2007
DOI: 10.1523/jneurosci.3168-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Inhibition of Orexigenic Hypothalamic Arcuate Nucleus Neurons Independently of Leptin Receptor/STAT3 Signaling

Abstract: Leptin directly suppresses the activity of orexigenic neurons in the hypothalamic arcuate nucleus (ARC). We examined c-Fos-like immunoreactivity (CFLIR) as a marker of ARC neuronal activity in db/db mice devoid of the signaling form of the leptin receptor (LRb) and s/s mice that express LRb S1138 [which is defective for STAT3 (signal transducer and activator of transcription) signaling]. Both db/db and s/s animals are hyperphagic and obese. This analysis revealed that CFLIR in agouti related peptide-expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 45 publications
2
69
1
1
Order By: Relevance
“…Leptin (100 nM) increased the firing rate in 12 of 13 POMC neurons (artificial cerebrospinal fluid [ACSF], 1.2 ± 0.1 Hz; leptin, 3.4 ± 0.4 Hz; n = 12, P = 0.00003; Figure 1A). Similar to previous reports, the leptin-induced increase in firing rate was reversible within approximately 15 minutes (12,13,31,32). The selective PI3K antagonist wortmannin (100 nM) was used to delineate a PI3K contribution to the leptin-induced excitation of POMC neurons.…”
Section: Pi3k Blockade Inhibits Leptin-induced Activation Of Pomc Neusupporting
confidence: 57%
“…Leptin (100 nM) increased the firing rate in 12 of 13 POMC neurons (artificial cerebrospinal fluid [ACSF], 1.2 ± 0.1 Hz; leptin, 3.4 ± 0.4 Hz; n = 12, P = 0.00003; Figure 1A). Similar to previous reports, the leptin-induced increase in firing rate was reversible within approximately 15 minutes (12,13,31,32). The selective PI3K antagonist wortmannin (100 nM) was used to delineate a PI3K contribution to the leptin-induced excitation of POMC neurons.…”
Section: Pi3k Blockade Inhibits Leptin-induced Activation Of Pomc Neusupporting
confidence: 57%
“…Serum leptin levels in normal subjects are of 11.5 (6.35 -20) ng/mL and in obese adults, 22 (13.5 -44) ng/mL, i.e., the serum leptin levels are significantly increased in obeses [83]. At the level in the arcuate nucleus of the hypothalamus revascularized by the omentum [5,19,84], leptin exerts an inhibitory action on the leptin receptor in the neuropeptide Y (NPY) and Agouti-relat-…”
Section: Leptinmentioning
confidence: 99%
“…The indirect nature of AgRP/NPY regulation via ER␣ prompted us to investigate whether estrogen would suppress AgRP/NPY function by inhibiting their neuronal activities. It is known that AgRP/NPY neurons are activated upon fasting, which is associated with dramatic induction of c-Fos expression in these neurons (25). By using Tg.NPY-hrGFP mice, we found that c-Fos expression was barely detectable in AgRP/NPY neurons in fed females (Fig.…”
Section: E2 Inhibits Fasting-induced C-fos Activation In Agrp/npy-neumentioning
confidence: 99%